Pengaruh Pendekatan PMRI Terhadap Hasil Belajar Siswa Pada Materi Persen di SD Negeri 117 Palembang - Islamy, Diah Putri (PHI: Jurnal Pendidikan Matematika, 2022)
Percentage is one of the basic mathematical material that often appears in human life. Especially in the economic and educational aspects, the word percent is often associated with finance. So, as early as possible students should understand the meaning of percentages in mathematics lessons. This strong understanding of the material will encourage students to be able to solve percent problems in mathematics. However, in reality, student learning outcomes at SD Negeri 117 Palembang are relatively low because more than 50% of students get scores below the KKM. One of the causes is the students' lack of understanding of the percent material and the less effective learning process. The learning process using the PMRI approach is one method to bridge the problems of the conventional teaching and learning process. This study used a pre-experimental design method which was carried out on 40 fifth grade students at SD Negeri 117 Palembang. The data used in this study is using the results of students' ability tests pre-test (before being treated) and post-test (after being given treatment). The purpose of this study was to determine whether there was an effect of learning outcomes in SD Negeri 117 using the PMRI approach. The results showed that there was an effect of student learning outcomes using the PMRI approach on the percent material. Based on the results of statistical testing using SPSS that the value of tcount > ttable  value, where the value of t count is 10,673 and t table is 2,306. Student learning outcomes also increased, namely by 85% of students getting scores above the KKM.